Behaviours in avoiding indoor exposure to second-hand smoke among pregnant women in five geographical areas of China: a cross-sectional study. (October 2016) - Xu, Xianglong; Rao, Yunshuang; Sharma, Manoj; Guo, Jeff J; Zhao, Yong
Abstract: Background: Second-hand smoke is a major indoor pollutant that causes serious health problems, especially for pregnant women. The 2010 Global Adult Tobacco Survey in China reported that 65·1% of non-smoking women of childbearing age were exposed to second-hand smoke at home and 52·6% were exposed in the workplace. This study aimed to probe behaviours in avoiding indoor second-hand smoke exposure induced by different intimate relationships among pregnant women in China. Methods: In this cross-sectional study, 2345 pregnant women aged 18 years and older surveyed in person by investigators from June 1, to Aug 31, 2015, from 16 hospitals in five provinces of Mainland China (Chongqing, Chengdu, Zunyi, Liaocheng, and Tianjin). We excluded women with serious complications or cognitive disorders. We divided measures taken by pregnant women in the face of indoor second-hand smoke into five categories "open a window to improve ventilation", "walk away", "dissuade", "ignore", and "not applicable". The "different intimate relationship" included a stranger, friend, colleague, father-in-law, mother-in-law, father, mother, and husband. All subjects gave their informed consent for inclusion before they participated in the study. The study protocol was approved by the Ethics Committee of Chongqing Medical University (record number 2015008). Findings: 2345 pregnant women were included for this study. Of these, the number of women who chose to walk away often in front of stranger (1710 [73%]) or a friend (854 [36%]) was lower than the number of those who chose to walk away often from their mother (400 [17%]) or husband (461 [20%]). They choose to open a window more often in front of a friend (373 [16%]) or colleague (299 [13%]), and less often in front of their mother-in-law (122 [5%]) or mother (107 [5%]). They choose to ignore more often in front of a stranger (105 [5%]) or a colleague (61 [3%]), and less often in front of their mother (43 [2%]) or husband (41 [2%]). They choose to dissuade more often in front of a colleague (870 [37%]) or their husband (807 [34%]), and less often in front of their mother-in-law (410 [17%]) or mother 442 [19%]). Interpretation: This study provides detailed information of the implications for indoor tobacco control. Of the family members, those for whom the pregnant women avoided the least second-hand smoke indoors were both mother-in-law and mother. The reason might be the sensitive relationship between mother-in-law and daughter-in-law in China. Funding: This project was supported by theMedjaden Academy & Research Foundation for Young Scientists (MJR20150047 ).